1988
DOI: 10.1002/ajmg.1320290214
|View full text |Cite
|
Sign up to set email alerts
|

Multiple “marker” chromosomes: A novel cytogenetic finding in a patient with mental retardation and congenital anomalies

Abstract: A patient with mental retardation and clinical manifestations suggestive of Noonan syndrome was found to have in her peripheral lymphocytes multiple small accessory marker chromosomes, varying in number from one to five per cell and in size from about half the size of the q arm of a G group chromosome to less than a centromere. Occasionally, in the more elongated markers, a G-positive or a C-positive band could be identified, or the marker had the appearance of a ring. The origin and significance of these mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…As the patient with four SACs had the more severe phenotype in an overall study of patients with SACs (Plattner et al 1993), it was suggested that in the presence of more SACs the phenotypic effect will be worse. Also, in the two other cases with multiple SACs, a phenotypic abnormality was observed (Mascarello et al 1987;Tozzi et al 1988). However, the present patient has no dysmorphism and is only mildly mentally retarded, which, considering the family history of this patient, may not even be related to the presence of the SACs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As the patient with four SACs had the more severe phenotype in an overall study of patients with SACs (Plattner et al 1993), it was suggested that in the presence of more SACs the phenotypic effect will be worse. Also, in the two other cases with multiple SACs, a phenotypic abnormality was observed (Mascarello et al 1987;Tozzi et al 1988). However, the present patient has no dysmorphism and is only mildly mentally retarded, which, considering the family history of this patient, may not even be related to the presence of the SACs.…”
Section: Discussionmentioning
confidence: 81%
“…To our knowledge, only four other studies document the presence of four or more SACs (Tozzi et al 1988;Mascarello et al 1987;Plattner et al 1993;Ulmer et al 1997). As in our case, the SACs identified by Plattner et al (1993) and Ulmer et al (1997) are also derived from different centromeric regions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Instability of ring chromosomes is a possible mechanism for duplication or rearrangement of chromosomes, and accounts for some reported cases of patients with two chromosomes of the same origin (e.g., [Fang et al, 1995] and case 10 from [Callen et al, 1991]). Initially, it was considered as a possible explanation for multiple markers of different morphology [Mascarello et al, 1987; Tozzi et al, 1988], but when the application of fluorescence in situ hybridization allowed determination of the origin of these supernumerary markers, it became clear that nearly all cases with multiple markers involved different chromosomes and, accordingly, independent origins.…”
Section: Discussionmentioning
confidence: 99%
“…The patient of Mascarello et al is 5 years old and has mostly 2 or 3 markers per cell. The 28-year-old patient of Tozzi et al [1988] has mostly 3 or 4 markers per cell. This apparently normal distribution suggests that the mitotic division and segregation of the markers probably occur in a random fashion.…”
mentioning
confidence: 99%